Analgesic and Anti-Pyretic Activities of the Root Bark of Rutidea Parviflora (Rubiaceae) - Johnson-Ajinwo Okiemute Rosa; Nyodee Dummene Godwin; Iso-Emi Bandele Agborubere (Journal of Advanced Pharmaceutical Science And Technology, 2021)
This study aims at investigating the antipyretic activity of different solvent fractions of the root bark of Rutideaparviflora(Rubiaceae). This plant is used ethno-botanically by the people of Ethiope East-West Local Government Area of Delta State, Nigeria to treat various ailments such as inflammation, fever and pain. This necessitated this research to validate its local use, due to the scanty literature and information present about this plant. It has also shown some anti-cancer and anti-inflammatory activity in previous researches. The present study is a randomized control study. Acetic acid induced writhing was employed for analgesic testing. Acetic acid was used to induce writhing in Wistar rats which were divided into fourteen (14) groups. The groups were administered extracts and fractions of the plant (200 mg/kg and 400 mg/kg). The animals were observed for number of writing movements and the percentage writhing was calculated. Baker’s yeast induced pyrexia was employed for the antipyretic testing. The animal groups were administered extracts and fractions of the plant (200 mg/kg and 400 mg/kg), with Paracetamol as the standard drug (100 mg/kg) and Normal saline (control) for both experiments. The body temperature of the rats was measured rectally over a period of five (5) hours. All values of P<0.05 were taken as significant. The organic extract, aqueous extract and various fractions (n-hexane, ethyl-acetate, n-butanol and aqueous) produced significant inhibition of writhing responses and pyrexia in a dose dependent manner and time dependent manner respectively. The aqueous extract at a dose of 400mg/kg showed the greatest reduction in writhing, 91.58% compared to the standard drug (paracetamol) which may suggest that the fraction possesses better efficacy than paracetamol as an analgesic. The observed activities could be attributed to these bioactive compounds: Palmatine, Urs-12-ene-24-oic-3-oxo-methyl ester and Gallic acid contained in R. parviflora.
Keywords: Rutideaparviflora